Trading price action reversals : technical analysis of price charts bar by bar for the serious trader - Brooks, Al, 1952- (Wiley trading series., 2012)
A detailed guide to profiting from trend reversals using the technical analysis of price actionThe key to being a successful trader is finding a system that works and sticking with it. Author Al Brooks has done just that. By simplifying his trading system and trading only 5-minute price charts he's found a way to capture profits regardless of market direction or economic climate. His first book, Reading Price Charts Bar by Bar, offered an informative examination of his system, but it didn't allow him to get into the real nuts and bolts of the approach.